Preferensi Nomadic Tourists Dalam Memilih Akomodasi di Bali - Putri, Ni Luh Emi Utami; Negarayana, Ida Bagus Putra; Liestiandre, Hanugerah Kristiono (Journal of Applied Science in Tourism Destination, 2024)
Bali is refocusing into a quality tourist destination to restore tourism after Covid-19 pandemic. Nomadic Tourism is one of the tourism potentials that can be developed. Digital Nomads are people who live in a nomadic way while working remotely using technology and the internet. The purpose of this research is to determine the preferences of Nomadic Tourists in choosing accommodation. This research uses seven attributes, including room, location, service & facilities, food & beverage, cleanliness, security, and value/price. This research uses a quantitative descriptive approach, using conjoint analysis. Collecting data using a questionnaire with a sample of 272 respondents, the sample in this research is divided into two categories, which are Asian Tourist and Western Tourist. The results of this research indicate that there are similarities between Asian Tourists and Western Tourists, which they consider value/price the most in choosing accommodation. The next attribute they consider is security, room, and then cleanliness. There is a difference between Asian and Western Tourists in considering the 5th and 6th attributes. Asian Tourists is more concerned with services & facilities and then location, while Western Tourists is more concerned with location and then services & facilities. The least considered attribute in accommodation selection is food & beverage.